2020
DOI: 10.1007/s40200-020-00498-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum sestrin 2 and betatrophin with serum neutrophil gelatinase associated lipocalin levels in type 2 diabetic patients with diabetic nephropathy

Abstract: Purpose Understanding the pathogenesis and the molecular mechanisms of diabetic nephropathy (DN) helps its timely detection and prevention. The current work aims tomeasure serum sestrin 2 and betatrophin levels in healthy and type diabetic (T2DM)subjects with/or without diabetic nephropathy (DN) and also to test their correlation with serum neutrophil gelatinase associated lipocalin (sNGAL); indicator of DN. Methods This study included 96 subjects; 20 healthy (G1) and 76 T2DM [22 normoalbuminuric (G2), 35 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…The results of the current work agree with the results of Mohany and Al Rugaie [2020] who found significant lower levels of serum sestrin2 in patients with T2DM than the healthy control group [50]. Also, they agree with Sundararajan et al [2020] who reported low serum sestrins levels in patients with dyslipidemia and T2DM and these levels correlated negatively with atherogenic factors and the severity of atherogenic index [51].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current work agree with the results of Mohany and Al Rugaie [2020] who found significant lower levels of serum sestrin2 in patients with T2DM than the healthy control group [50]. Also, they agree with Sundararajan et al [2020] who reported low serum sestrins levels in patients with dyslipidemia and T2DM and these levels correlated negatively with atherogenic factors and the severity of atherogenic index [51].…”
Section: Discussionsupporting
confidence: 91%
“…et al, 2015;Ro et al, 2016;Segales et al, 2020;Sundararajan et al, 2020). In recent human studies, secreted Sestrin2 level in the serum of obese children, diabetic nephropathy patients, and elderly sarcopenia adults is significantly lower and associated with metabolic dysfunction (Nourbakhsh et al, 2017;Mohany and Al Rugaie, 2020;Rajan et al, 2020), suggesting that the expression or the secretion of Sestrin2 is somehow blocked in the disease state. Measuring tissue-or individual patient-specific Sestrins level could be used as a direct health or stress sensors, and proper timely administration of active Sestrins would be emerging preventive or therapeutic methods for those who are suffering from metabolic diseases and aging-associated pathologies.…”
Section: Perspective On Sestrins As Stress Sensing-proteins In Metabomentioning
confidence: 99%
“…MicroRNAs are small non-coding RNAs that regulates the gene expression post-transcriptionally either by preventing the translation of their targeted mRNAs or by degrading them [ 9 ]. They have a recognizable role in pathogenesis, prevention and diagnosis of many diseases including obesity and diabetes mellitus [ 5 , 10 12 ]. In the current study, the circulating microRNA-486, −146b and -15b levels are found to be higher in obese children with/without T2DM than the healthy control.…”
Section: Discussionmentioning
confidence: 99%
“…They negatively regulate mRNAs translation or enhance their degradation [ 9 ]. Abnormal expression of microRNAs participates in the pathogenesis of many adverse events such as obesity, dyslipidemias, impaired glucose tolerance and diabetes mellitus [ 5 , 10 12 ]. The exact role of microRNAs in obese and/or diabetic children is still under investigations.…”
Section: Introductionmentioning
confidence: 99%